A Rare SPRY4 Gene Mutation Is Associated With Anosmia and Adult-Onset Isolated Hypogonadotropic Hypogonadism - Indirli, Rita; Cangiano, Biagio; Profka, Eriselda; Mantovani, Giovanna; Persani, Luca; Arosio, Maura; Bonomi, Marco; Ferrante, Emanuele (Frontiers in Endocrinology, 2019)
Background: Isolated hypogonadotropic hypogonadism (IHH) is a rare, clinically heterogeneous condition, caused by the deficient secretion or action of gonadotropin releasing hormone (GnRH). It can manifest with absent or incomplete sexual maturation, or as infertility at adult-age; in a half of cases, IHH is associated with hypo/anosmia (Kallmann syndrome). Although a growing number of genes are being related to this disease, genetic mutations are currently found only in 40% of IHH patients. Case description: Severe congenital hyposmia was diagnosed in a 25-year-old Caucasian man referred to the Ear-Nose-Throat department of our clinic. The patient had no cryptorchidism or micropenis and experienced a physiological puberty; past medical history and physical examination were unremarkable. Olfactory structures appeared hypoplasic, while hypothalamus, pituitary gland, and stalk were normal on MRI (neuroradiological imaging); testosterone levels, as well as pulsatile gonadotropin secretion and other pituitary hormones were unaffected at the time of first referral. At the age of 48, the patient returned to our clinic for sexual complaints, and the finding of low testosterone levels (6.8 and 5.8 nmol/L on two consecutive assessments) with inappropriately normal gonadotropin levels led to the diagnosis of hypogonadotropic hypogonadism. GnRH test was consistent with hypothalamic origin of the defect. Next generation sequencing was then performed revealing a rare heterozygous allelic variant in SPRY4 gene (c.158G>A, p.R53Q). The biological and clinical effects of this gene variant had never been reported before. A diagnosis of Kallmann syndrome was finally established, and the patient was started on testosterone replacement therapy. Conclusion: This case describes the clinical phenotype associated with a rare SPRY4 gene allelic variant, consisting in congenital severe smell defect and adult-onset IHH; in patients with apparently isolated congenital anosmia genetic analysis can be valuable to guide follow up, since IHH can manifest later in adulthood. Characterization of other modifying genes and acquired environmental factors is needed for a better understanding of the physiopathology and clinical manifestations of this disease.